Character Building Profile of Pancasila Students As An Effort to Realize National Character - Hasbi, Muhammad; Muktamar, Ahmad; Fitri, Fitri (ETDC: Indonesian Journal of Research and Educational Review, 2023)
In an attempt to realize national character, the purpose of this research is to identify the characteristics of Pancasila learners. A library method approach was employed in this study's methodology. The study's findings demonstrate that one of the strategies promoting the accomplishment of national education objectives and the ongoing implementation of the character-building initiative is the Pancasila student profile. The Pancasila student profile outlines the qualities and aptitudes Indonesian students need to possess in order to succeed in school and integrate into society. Using the six dimensions of the Pancasila student profile—faith and devotion to God Almighty, global diversity, independence, mutual cooperation, critical reasoning, and creativity—it is hoped that the Indonesian people will grow into intelligent, polite people capable of facing the challenges of the twenty-first century. They will also, of course, instill the values found in Pancasila, as our nation's philosophy is consistent and can ultimately fulfill one of the 1945 Constitution's mandates: create a prosperous and dignified national life. A key component of the approach for creating Pancasila student profiles is the integration of co-curricular and extracurricular activities into project-based formal education activities in order to enhance the profile of Pancasila students. It is envisaged that the Pancasila student profile strategy will enable the development of an exceptional Indonesian national character that can compete on a global scale.